Traditional botanical knowledge: food plants from the Huni Kuĩ indigenous people, Acre, western Brazilian Amazon - Pilnik, Málika Simis; Argentim, Tarik; Kinupp, Valdely Ferreira; Haverroth, Moacir; Ming, Lin Chau [UNESP] (FapUNIFESP (SciELO), 2023)
The Kaxinawá indigenous people (auto-identified as the Huni Kuĩ) are native to the western Amazon, on the Brazilian border with Peru, and have an extensive biodiversity-related knowledge, which is parti of a coherent social-ecological system. Our study investigated native knowledge of edible forest plants, in three communities within the Kaxinawá Indigenous Land on the Lower Rio Jordão, Acre state, Brazil. The principal methods used were participant observation, open and semi-structured interviews and walk-in-the-woods. The study recorded 89 native food species. Some 60% are managed in food-production areas, with 56% of the recorded species have received little or no scientific study of their food potential. The role which natural systems play in Huni Kuĩ society is indicated by the management and use of a high diversity of native species, which contributes to food security and nutritional sovereignty. However, there is a progressive under-utilization and substitution of forest species, due to the introduction of cultivated exotic species and the increase in consumption of industrialized products. An enhancement of the value given to native food-plants is needed to encourage continuing autonomy of production, and diet diversification, as well as the conservation of sociobiodiversity of traditional peoples in the Amazon through sustainable management practices of the current social-ecological system.
Keywords: Amazon; ethnobotany; food plants; indigenous knowledge; management and use; sociobiodiversity conservation; transdisciplinarity